Investigating beach erosion and deposition patterns around Saldanha Bay by mapping naturally occurring radionuclides - Sehone, Alfred Mogotsi (Stellenbosch : Stellenbosch University, 2025)
Thesis (MMil)--Stellenbosch University, 2025.